THE IMPROVEMENT OF PHYSICAL CULTURE TEACHERS TRAINING SYSTEM - Aleksey G. Polivaev (Высшее образование в России)
The article analyzes the problem of raising the quality of training students at faculties of physical education of pedagogical colleges. The paper presents the experience of organizing training process at the faculty of physical education of P.P. Ershov Ishim State Teacher’s Training Institute considering individual psychological peculiarities of students and their suitability for the requirements of teacher’s profession. The article suggests the ways of improving the education quality of teachers training based on selection and organization of learning process considering students’ personal characteristics.